A bio-based gel composition and its preparation method and application

By using low acyl gellan gum and high acyl gellan gum in the bio-based gellan gum composition, as well as the combination of epoxy block copolymers with different weight average molecular weights and alkyl glycosides, the problem of insufficient stability of traditional bead colloidal wall materials is solved, and higher stability and corrosion resistance are achieved, and production efficiency and product safety are improved.

CN118956013BActive Publication Date: 2025-05-02JIANGSU BAOLAIYA NEW MATERIAL TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411122519.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2025-05-02
Estimated Expiration
2044-08-15

AI Technical Summary

Technical Problem

The wall stability of traditional bead colloids is insufficient, which leads to prone to deterioration or corrosion during preparation and storage, affecting product quality and safety, and limiting production efficiency and sustainability.

Method used

The combination of low acyl gellan gellan gellan gellan gellan gellan gellan gellan gellan gellan is used to combine the combination of epoxy block copolymers with different weight average molecular weights and alkyl glycosides to form a stable sol system and a tightly entangled internal network to enhance the cohesiveness and corrosion resistance of the colloid.

Benefits of technology

The stability and corrosion resistance of bio-based gel compositions and bead-burned colloids are significantly improved, spoilage and corrosion-induced phenomena are avoided, production efficiency is improved, and product safety and sustainability are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118956013B_ABST
    Figure CN118956013B_ABST
Patent Text Reader

Abstract

The present application relates to the field of bio-based gel compositions, and in particular to a bio-based gel composition and its preparation method and application. The bio-based gel composition, in parts by mass, includes raw materials such as: 50-70 parts of main glue, 25-35 parts of auxiliary glue, 2-10 parts of metal compounds, 10-50 parts of additives, 10-20 parts of filler particles, and 1600-1800 parts of deionized water. The bio-based gel composition obtained in the present application can not only meet the safety requirements of existing consumers, but also further improve its own stability level, thereby effectively avoiding the deterioration and corruption of the blasting bead colloid during the preparation and storage and transportation of the finished product while improving the various properties of the blasting bead colloid itself, and greatly improving the production efficiency of the blasting bead colloid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of organic polymer compositions, and in particular to a bio-based gel composition and a preparation method and application thereof. Background Art

[0002] Bio-based gel compositions are three-dimensional network structures composed of naturally derived polymers with unique physical and chemical properties. These materials have been widely used in pharmaceutical products, daily necessities, daily chemical products, agriculture, and personal care products due to their excellent biocompatibility, biodegradability, and customizability.

[0003] In the application field of bio-based gel compositions, popping bead colloids are an innovative material that can be embedded with multiple scent capsules or scent liquids to add unique functions and experiences to products. In the daily chemical products, tobacco and other industries, popping bead colloids adjust the texture of products, release active ingredients, and enhance consumers' interactive experience through their unique release mechanism.

[0004] Although bio-based gel compositions and their derived popping colloids have shown great potential in multiple industries, existing technologies still face some key challenges. In particular, the wall materials of traditional popping colloids, such as plant colloids and starch, are not stable enough, which has become a significant problem during the preparation and storage process, easily leading to product deterioration or corruption, seriously affecting the quality and safety of the products. In addition, these stability issues also limit production efficiency, increase the complexity of logistics and storage, and have an adverse impact on the economic benefits of enterprises and the sustainability of products.

[0005] Therefore, in order to solve the above problems, the present application provides a bio-based gel composition and a preparation method thereof. The bio-based gel composition obtained in the present application can not only meet the current safety requirements of consumers, but also further improve its own stability level. Therefore, on the premise of improving the various properties of the bio-based gel composition and the popping bead colloid itself, the deterioration and corruption of the bio-based gel composition and the popping bead colloid during the preparation and storage and transportation of the finished products can be effectively avoided, and the production efficiency of the above products can be greatly improved.

[0006] In order to solve the above problems, the first aspect of the present application provides a bio-based gel composition, which includes, by mass, 50 to 70 parts of main glue, 25 to 35 parts of auxiliary glue, 2 to 10 parts of metal compounds, 10 to 50 parts of additives, 10 to 20 parts of filling particles, and 1600 to 1800 parts of deionized water.

[0007] As a preferred solution, the mass ratio of the main glue to the auxiliary glue is (5-6): (2.5-3).

[0008] As a preferred solution, the main gel is carrageenan and agar.

[0009] As a preferred solution, the mass ratio of carrageenan to agar is (3-6):(1-4).

[0010] As a preferred solution, the mass ratio of carrageenan to agar is (3.5-4.5):(1.5-2).

[0011] As a preferred solution, the mass ratio of carrageenan to agar is 4:(1.5-1.8).

[0012] As a preferred solution, the auxiliary gum is a combination of low acyl gellan gum and high acyl gellan gum.

[0013] As a preferred solution, the mass ratio of the low acyl gellan gum to the high acyl gellan gum is (2-4):(0.05-0.5).

[0014] As a preferred solution, the mass ratio of the low acyl gellan gum to the high acyl gellan gum is (2.5-3.2):(0.05-0.2).

[0015] As a preferred solution, the mass ratio of the low acyl gellan gum to the high acyl gellan gum is 2.9:0.1.

[0016] In the present application, by adopting the above-mentioned low-acyl gellan gum and high-acyl gellan gum compound, a stable sol system can be effectively formed in the preparation process of the bio-based gel composition, and the obtained bio-based gel composition and its bursting beads have excellent storage and transportation stability. This is mainly because the polymer chain of high-acyl gellan gum and the acyl groups on its molecular chain can greatly enhance the cohesion of the internal system of the colloid, and the high viscosity and rapid solidification characteristics of the added low acyl group can form a good entangled molecular chain network in the colloid system while ensuring the gel efficiency of the colloid, and then complete the preparation of the colloid in a short time, thereby reducing the contact degree and frequency of the original colloid material with the external pollution source, and then effectively isolate the invasion of foreign matter from the outside after the gel preparation is completed, so as to obtain good mechanical and viscosity properties while maintaining excellent stability and corrosion resistance.

[0017] As a preferred solution, the metal compound is at least one of sodium chloride, potassium chloride, calcium chloride, sodium carbonate, sodium bicarbonate, and magnesium chloride.

[0018] As a preferred solution, the metal compound is potassium chloride and calcium chloride.

[0019] As a preferred solution, the mass ratio of potassium chloride to calcium chloride is (2-5):(0.1-1).

[0020] As a preferred solution, the mass ratio of potassium chloride to calcium chloride is (3-4):(0.5-1).

[0021] As a preferred solution, the mass ratio of potassium chloride to calcium chloride is 3.5:0.5.

[0022] As a preferred solution, the average particle size of the metal compound is 0.05-0.3 μm.

[0023] As a preferred solution, the average particle size of the metal compound is 0.1-0.2 μm.

[0024] As a preferred solution, the auxiliary agents are water retaining agents and surfactants.

[0025] As a preferred solution, the mass ratio of the water retaining agent to the surfactant is (1.5-3):1.

[0026] As a preferred solution, the water retaining agent is sodium alginate, glycerol and sorbitol.

[0027] As a preferred solution, the mass ratio of sodium alginate, glycerol and sorbitol is (0.3-7): (6-30): (3-20).

[0028] As a preferred solution, the mass ratio of sodium alginate, glycerol and sorbitol is (1-3): (10-15): (5-10).

[0029] As a preferred solution, the mass ratio of sodium alginate, glycerol and sorbitol is (1.5-2): (12-14): (6-8).

[0030] As a preferred solution, the surfactant is a block copolymer and an alkyl glycoside.

[0031] As a preferred solution, the mass ratio of the block copolymer to the alkyl glycoside is (1-3):(3-8).

[0032] As a preferred solution, the mass ratio of the block copolymer to the alkyl glycoside is (1.5-2.5):(4-7).

[0033] As a preferred solution, the mass ratio of the block copolymer to the alkyl glycoside is 2:6.5.

[0034] As a preferred solution, the block copolymer is an epoxy block copolymer.

[0035] As a preferred solution, the weight average molecular weight of the epoxy block copolymer is 2500 to 10000 Da.

[0036] As a preferred solution, the epoxy block copolymer is a composition of an epoxy copolymer with a weight average molecular weight of 2500-3000Da and an epoxy copolymer with a weight average molecular weight of 6000-8000Da, and the mass ratio of the two is (1-2.5): (0.1-1).

[0037] As a preferred solution, the mass ratio of the epoxy copolymer with a weight average molecular weight of 2500-3000 Da to the epoxy copolymer with a weight average molecular weight of 6000-8000 Da is (1.5-2):(0.4-0.8).

[0038] As a preferred solution, the polymerization degree of the alkyl glycoside is 2 to 3.5.

[0039] In the present application, by using a combination of epoxy block copolymers and alkyl glycosides with different weight average molecular weights, the stability, corrosion resistance and suitable mechanical properties of the bio-based gel composition can be greatly improved. In the present application, the epoxy block copolymers and alkyl glycosides used can not only show good surface activity in the gel system, but also promote the epoxy block copolymers and alkyl glycosides of different molecular weights to be arranged in layers on the surface of the raw material, making it easier to form a multilayer structure for the wrapping of the raw material, increasing the interfacial viscosity during the preparation process, and ensuring good interfacial resistance even in the process of preparing the glue at high temperature, thereby avoiding excessive collisions of active molecules and invasion of foreign matter from the outside; on the other hand, in the colloid after preparation, the presence of the above-mentioned epoxy block copolymers and alkyl glycosides can also form a tightly entangled internal network in the colloid system, reducing the movement rate of microbial molecules and active molecules in the colloid system, increasing their movement resistance, and even in the case of high molecular activity (high temperature), the degree and frequency of collisions between active molecules can be weakened, thereby obtaining excellent stability.

[0040] As a preferred solution, the filler particles are modified titanium oxide particles; the preparation method of the modified titanium oxide particles comprises the following steps: S1: adding titanium oxide and ammonia water into anhydrous ethanol and stirring to mix evenly; S2: dropping an aqueous solution of ethyl orthosilicate into the mixture obtained in S1, the dropping reaction time is 2 to 3 hours, and the dropping reaction temperature is 50 to 55°C;

[0041] S3: After the dropwise addition reaction is completed, centrifuge, wash with anhydrous ethanol and dry to obtain a solid powder.

[0042] The second aspect of the present application provides a method for preparing the above-mentioned bio-based gel composition, which comprises the following steps: S1: adding the required ingredients to the sol in the gelling tank for mixing, the mixing temperature being 80-90°C, after the mixing is completed, adding to a pill-dropping machine and adding flavor to prepare wet pills; S2: placing the wet pills in a pill washing barrel for washing, after the washing is completed, transferring to a ventilated cage for drying at 50-60°C; S3: after the drying is completed, transferring to a vibrating sieving machine for sieving 1-50 mesh as required, after the completion, the bio-based gel composition is obtained.

[0043] As a preferred solution, the flavor is at least one of a plant flavor, a flower flavor, a fruit and vegetable flavor, and a wine flavor.

[0044] The second aspect of the present application provides an application of the above-mentioned bio-based gel composition, including application of the bio-based gel composition in the preparation of explosive beads.

[0045] The beneficial effects of this application are:

[0046] 1. The bio-based gel composition provided in the present application can not only meet the safety requirements of existing consumers, but also further improve its own stability level, thereby effectively avoiding the deterioration and corruption of the bursting bead colloid during the preparation and storage and transportation of the finished product while improving the various properties of the bursting bead colloid itself, and greatly improving the production efficiency of the bursting bead colloid.

[0047] 2. A bio-based gel composition provided in the present application is compounded with low-acyl gellan gum and high-acyl gellan gum, which can effectively form a stable sol system during the preparation process of the bio-based gel composition, and the prepared bio-based gel composition and its bursting beads have excellent storage and transportation stability; the polymer chains possessed by high-acyl gellan gum and the acyl groups on its molecular chains can greatly enhance the cohesion of the internal system of the colloid, and the high viscosity and rapid curing properties of the added low-acyl groups can form a good entangled molecular chain network in the colloid system while ensuring the gelation efficiency of the colloid, thereby completing the preparation of the colloid in a short time, thereby reducing the degree and frequency of contact between the original colloid material and external pollution sources, and effectively isolating the invasion of external foreign matter after the gel preparation is completed.

[0048] 3. A bio-based gel composition provided in the present application can greatly improve the stability, corrosion resistance and suitable mechanical properties of the bio-based gel composition by adopting a combination of epoxy block copolymers and alkyl glycosides with different weight-average molecular weights; in addition to being able to exhibit good surface activity in the gel system, the combination of the epoxy block copolymers and alkyl glycosides can also promote the layered arrangement of epoxy block copolymers and alkyl glycosides with different molecular weights on the surface of the raw material, making it easier to form a multi-layer structure to wrap the raw material, increasing the interfacial viscosity during the preparation process, and ensuring good interfacial resistance even in the high-temperature preparation process, thereby avoiding excessive collisions of active molecules and invasion of foreign matter.

[0049] 4. A bio-based gel composition provided in the present application adopts a combination of epoxy block copolymers with different weight-average molecular weights and alkyl glycosides, which can also form a tightly entangled internal network in the colloid after preparation, thereby reducing the movement rate of microbial molecules and active molecules in the colloid system and increasing their movement resistance. Even when the polymer is active (high temperature), it can also weaken the degree and frequency of collisions between active molecules, thereby obtaining excellent stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 The infrared Fourier transform infrared (FTIR) spectrum of carrageenan and agar in Example 1 of the present invention is shown in FIG.

[0051] Figure 2 The XRD patterns of potassium chloride and calcium chloride in Example 1 of the present invention are shown in FIG. DETAILED DESCRIPTION

[0052] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0053] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0054] Example 1

[0055] Example 1 The first aspect provides a bio-based gel composition, in which the raw materials include, by mass: 55 parts of main glue, 25 parts of auxiliary glue, 4 parts of metal compound, 30 parts of auxiliary agent, 10 parts of filling particles, and 1650 parts of deionized water.

[0056] The main gelatin is carrageenan and agar; carrageenan is purchased from the food-grade carrageenan products sold by Hubei Mingtuo Biotechnology Co., Ltd.; agar is purchased from the food-grade agar products sold by Wuhan Juxinlai Biotechnology Co., Ltd.; the mass ratio of carrageenan to agar is 4:1.5.

[0057] The auxiliary gum is a composition of low acyl gellan gum and high acyl gellan gum; the mass ratio of low acyl gellan gum to high acyl gellan gum is 2.9:0.1; low acyl gellan gum and high acyl gellan gum are purchased from food grade low acyl gellan gum and high acyl gellan gum products sold by Guangzhou Huayu Biotechnology Co., Ltd., respectively.

[0058] The metal compounds are potassium chloride and calcium chloride; the mass ratio of potassium chloride to calcium chloride is 3.5:0.5; and the average particle size of potassium chloride and calcium chloride is 0.1 μm.

[0059] The auxiliary agents are water retaining agent and surfactant; the mass ratio of the water retaining agent to the surfactant is 2:1.

[0060] The water retaining agent is sodium alginate, glycerol and sorbitol, and the mass ratio of the three is 2:13:8.

[0061] The surfactants are block copolymers and alkyl glycosides, and the mass ratio of the block copolymers to the alkyl glycosides is 2:5; the alkyl glycoside is purchased from the APG0810 model product sold by Shanghai Hongzhuang Chemical Technology Co., Ltd., and the average degree of polymerization of the alkyl glycoside is 2.5.

[0062] The block copolymer is a composition of epoxy block copolymers; the composition of the epoxy block copolymer is BASF L64 (weight average molecular weight 2900Da) and BASF L87 (weight average molecular weight 7800Da), and the mass ratio of the two is 1.8:0.5.

[0063] The filling particles are modified titanium oxide particles; the preparation method of modified titanium oxide particles comprises the following steps, measured in parts by mass: S1: adding 3 parts of titanium oxide and 10 parts of ammonia water into 50 parts of anhydrous ethanol, stirring and mixing evenly; S2: adding an aqueous solution containing 6 parts of ethyl orthosilicate (50 parts in total) dropwise into the mixture obtained in S1, the dropping reaction time is 2 hours, and the dropping reaction temperature is 50°C; S3: after the dropping reaction is completed, centrifuge and wash with anhydrous ethanol and then dry to obtain a solid powder.

[0064] The second aspect of this embodiment also provides a method for preparing the above-mentioned bio-based gel composition, which comprises the following steps: S1: adding the required ingredients to the sol in the gelling tank for mixing, the mixing temperature being 85°C, after the mixing is completed, adding to a pill-dropping machine and adding flavoring to prepare wet pills; S2: placing the wet pills in a pill washing barrel for washing, after the washing is completed, transferring to a ventilated cage for drying at 55°C; S3: after the drying is completed, transferring to a vibrating sieving machine for sieving 10 meshes as required, after the completion, the bio-based gel composition is obtained.

[0065] The flavor is sweet orange flavor; the added amount is 0.5wt% of the total amount of S1 sol.

[0066] Example 2

[0067] Example 2 The first aspect provides a bio-based gel composition, in which the raw materials include, by mass: 60 parts of main glue, 30 parts of auxiliary glue, 5 parts of metal compound, 30 parts of auxiliary agent, 12 parts of filling particles, and 1800 parts of deionized water.

[0068] The main gelatin is carrageenan and agar; carrageenan is purchased from the food-grade carrageenan products sold by Hubei Mingtuo Biotechnology Co., Ltd.; agar is purchased from the food-grade agar products sold by Wuhan Juxinlai Biotechnology Co., Ltd.; the mass ratio of carrageenan to agar is 4.5:2.

[0069] The auxiliary gum is a composition of low acyl gellan gum and high acyl gellan gum; the mass ratio of low acyl gellan gum to high acyl gellan gum is 2.9:0.1; low acyl gellan gum and high acyl gellan gum are purchased from food grade low acyl gellan gum and high acyl gellan gum products sold by Guangzhou Huayu Biotechnology Co., Ltd., respectively.

[0070] The metal compounds are potassium chloride and calcium chloride; the mass ratio of potassium chloride to calcium chloride is 4:0.8; and the average particle size of potassium chloride and calcium chloride is 0.1 μm.

[0071] The auxiliary agents are water retaining agent and surfactant; the mass ratio of water retaining agent to surfactant is 1.5:1.

[0072] The water retaining agent is sodium alginate, glycerol and sorbitol, and the mass ratio of the three is 2:13:8.

[0073] The surfactants are block copolymers and alkyl glycosides, and the mass ratio of the block copolymers to the alkyl glycosides is 2.5:4.5; the alkyl glycoside is purchased from the APG0810 model product sold by Shanghai Hongzhuang Chemical Technology Co., Ltd., and the average degree of polymerization of the alkyl glycoside is 2.5.

[0074] The block copolymer is a composition of epoxy block copolymers; the composition of the epoxy block copolymer is BASF L64 (weight average molecular weight 2900Da) and BASF L87 (weight average molecular weight 7800Da), and the mass ratio of the two is 1.8:0.5.

[0075] The filling particles are modified titanium oxide particles; the preparation method of modified titanium oxide particles comprises the following steps, measured in parts by mass: S1: adding 3 parts of titanium oxide and 10 parts of ammonia water into 50 parts of anhydrous ethanol, stirring and mixing evenly; S2: adding an aqueous solution containing 6 parts of ethyl orthosilicate (50 parts in total) dropwise into the mixture obtained in S1, the dropping reaction time is 2 hours, and the dropping reaction temperature is 50°C; S3: after the dropping reaction is completed, centrifuge and wash with anhydrous ethanol and then dry to obtain a solid powder.

[0076] The second aspect of this embodiment also provides a method for preparing the above-mentioned bio-based gel composition, which comprises the following steps: S1: adding the required ingredients to the sol in the gelling tank for mixing, the mixing temperature being 85°C, after the mixing is completed, adding to a pill-dropping machine and adding flavoring to prepare wet pills; S2: placing the wet pills in a pill washing barrel for washing, after the washing is completed, transferring to a ventilated cage for drying at 55°C; S3: after the drying is completed, transferring to a vibrating sieving machine for sieving 10 meshes as required, after the completion, the bio-based gel composition is obtained.

[0077] The flavor is sweet orange flavor; the added amount is 0.5wt% of the total amount of S1 sol.

[0078] Example 3

[0079] Example 3 The first aspect provides a bio-based gel composition, in which the raw materials include, by mass: 55 parts of main glue, 25 parts of auxiliary glue, 4 parts of metal compound, 30 parts of auxiliary agent, 10 parts of filling particles, and 1650 parts of deionized water.

[0080] The main gelatin is carrageenan and agar; carrageenan is purchased from the food-grade carrageenan products sold by Hubei Mingtuo Biotechnology Co., Ltd.; agar is purchased from the food-grade agar products sold by Wuhan Juxinlai Biotechnology Co., Ltd.; the mass ratio of carrageenan to agar is 4:1.5.

[0081] The auxiliary gum is a composition of low acyl gellan gum and high acyl gellan gum; the mass ratio of low acyl gellan gum to high acyl gellan gum is 2.9:0.1; low acyl gellan gum and high acyl gellan gum are purchased from food grade low acyl gellan gum and high acyl gellan gum products sold by Guangzhou Huayu Biotechnology Co., Ltd., respectively.

[0082] The metal compounds are potassium chloride and calcium chloride; the mass ratio of potassium chloride to calcium chloride is 3.5:0.5; and the average particle size of potassium chloride and calcium chloride is 0.1 μm.

[0083] The auxiliary agents are water retaining agent and surfactant; the mass ratio of the water retaining agent to the surfactant is 2:1.

[0084] The water retaining agent is sodium alginate, glycerol and sorbitol, and the mass ratio of the three is 3:10:6.

[0085] The surfactants are block copolymers and alkyl glycosides, and the mass ratio of the block copolymers to the alkyl glycosides is 1.5:6; the alkyl glycoside is purchased from the APG0810 model product sold by Shanghai Hongzhuang Chemical Technology Co., Ltd., and the average degree of polymerization of the alkyl glycoside is 2.5.

[0086] The block copolymer is a composition of epoxy block copolymers; the composition of the epoxy block copolymer is BASF L64 (weight average molecular weight 2900Da) and BASF L87 (weight average molecular weight 7800Da), and the mass ratio of the two is 1.5:0.7.

[0087] The filling particles are modified titanium oxide particles; the preparation method of modified titanium oxide particles comprises the following steps, measured in parts by mass: S1: adding 3 parts of titanium oxide and 10 parts of ammonia water into 50 parts of anhydrous ethanol, stirring and mixing evenly; S2: adding an aqueous solution containing 6 parts of ethyl orthosilicate (50 parts in total) dropwise into the mixture obtained in S1, the dropping reaction time is 2 hours, and the dropping reaction temperature is 50°C; S3: after the dropping reaction is completed, centrifuge and wash with anhydrous ethanol and then dry to obtain a solid powder.

[0088] The second aspect of this embodiment also provides a method for preparing the above-mentioned bio-based gel composition, which comprises the following steps: S1: adding the required ingredients to the sol in the gelling tank for mixing, the mixing temperature being 85°C, after the mixing is completed, adding to a pill-dropping machine and adding flavoring to prepare wet pills; S2: placing the wet pills in a pill washing barrel for washing, after the washing is completed, transferring to a ventilated cage for drying at 55°C; S3: after the drying is completed, transferring to a vibrating sieving machine for sieving 10 meshes as required, after the completion, the bio-based gel composition is obtained.

[0089] The flavor is sweet orange flavor; the added amount is 0.5wt% of the total amount of S1 sol.

[0090] Comparative Example 1

[0091] Comparative Example 1 The first aspect provides a bio-based gel composition, in which the raw materials include, by mass: 55 parts of main glue, 25 parts of auxiliary glue, 4 parts of metal compound, 30 parts of auxiliary agent, 10 parts of filling particles, and 1650 parts of deionized water.

[0092] The main gelatin is carrageenan and agar; carrageenan is purchased from the food-grade carrageenan products sold by Hubei Mingtuo Biotechnology Co., Ltd.; agar is purchased from the food-grade agar products sold by Wuhan Juxinlai Biotechnology Co., Ltd.; the mass ratio of carrageenan to agar is 4:1.5.

[0093] The auxiliary gum is a composition of low acyl gellan gum and high acyl gellan gum; the mass ratio of low acyl gellan gum to high acyl gellan gum is 1:1; low acyl gellan gum and high acyl gellan gum are purchased from food grade low acyl gellan gum and high acyl gellan gum products sold by Guangzhou Huayu Biotechnology Co., Ltd., respectively.

[0094] The metal compounds are potassium chloride and calcium chloride; the mass ratio of potassium chloride to calcium chloride is 3.5:0.5; and the average particle size of potassium chloride and calcium chloride is 0.1 μm.

[0095] The auxiliary agents are water retaining agent and surfactant; the mass ratio of the water retaining agent to the surfactant is 2:1.

[0096] The water retaining agent is sodium alginate, glycerol and sorbitol, and the mass ratio of the three is 2:13:8.

[0097] The surfactants are block copolymers and alkyl glycosides, and the mass ratio of the block copolymers to the alkyl glycosides is 2:5; the alkyl glycoside is purchased from the APG0810 model product sold by Shanghai Hongzhuang Chemical Technology Co., Ltd., and the average degree of polymerization of the alkyl glycoside is 2.5.

[0098] The block copolymer is a composition of epoxy block copolymers; the composition of the epoxy block copolymer is BASF L64 (weight average molecular weight 2900Da) and BASF L87 (weight average molecular weight 7800Da), and the mass ratio of the two is 1.8:0.5.

[0099] The filling particles are modified titanium oxide particles; the preparation method of modified titanium oxide particles comprises the following steps, measured in parts by mass: S1: adding 3 parts of titanium oxide and 10 parts of ammonia water into 50 parts of anhydrous ethanol, stirring and mixing evenly; S2: adding an aqueous solution containing 6 parts of ethyl orthosilicate (50 parts in total) dropwise into the mixture obtained in S1, the dropping reaction time is 2 hours, and the dropping reaction temperature is 50°C; S3: after the dropping reaction is completed, centrifuge and wash with anhydrous ethanol and then dry to obtain a solid powder.

[0100] The second aspect of the present comparative example also provides a method for preparing the above-mentioned bio-based gel composition, and the preparation method comprises the following steps: S1: adding the required ingredients to the sol in the gelling tank for mixing, and the mixing temperature is 85°C. After the mixing is completed, adding to the pill dropping machine and adding flavor to prepare wet pills; S2: placing the wet pills in a pill washing barrel for washing, and after the washing is completed, transferring to a ventilated rotating cage for drying at 55°C; S3: after the drying is completed, transferring to a vibrating sieving machine for sieving 10 meshes as required, and after completion, the bio-based gel composition is obtained.

[0101] The flavor is sweet orange flavor; the added amount is 0.5wt% of the total amount of S1 sol.

[0102] Comparative Example 2

[0103] Comparative Example 2 The first aspect provides a bio-based gel composition, in which the raw materials include, by mass: 55 parts of main glue, 25 parts of auxiliary glue, 4 parts of metal compound, 30 parts of auxiliary agent, 10 parts of filling particles, and 1650 parts of deionized water.

[0104] The main gelatin is carrageenan and agar; carrageenan is purchased from the food-grade carrageenan products sold by Hubei Mingtuo Biotechnology Co., Ltd.; agar is purchased from the food-grade agar products sold by Wuhan Juxinlai Biotechnology Co., Ltd.; the mass ratio of carrageenan to agar is 4:1.5.

[0105] The auxiliary gum is low acyl gellan gum; the low acyl gellan gum is purchased from the food grade low acyl gellan gum product sold by Guangzhou Huayu Biotechnology Co., Ltd.

[0106] The metal compounds are potassium chloride and calcium chloride; the mass ratio of potassium chloride to calcium chloride is 3.5:0.5; and the average particle size of potassium chloride and calcium chloride is 0.1 μm.

[0107] The auxiliary agents are water retaining agent and surfactant; the mass ratio of the water retaining agent to the surfactant is 2:1.

[0108] The water retaining agent is sodium alginate, glycerol and sorbitol, and the mass ratio of the three is 2:13:8.

[0109] The surfactants are block copolymers and alkyl glycosides, and the mass ratio of the block copolymers to the alkyl glycosides is 2:5; the alkyl glycoside is purchased from the APG0810 model product sold by Shanghai Hongzhuang Chemical Technology Co., Ltd., and the average degree of polymerization of the alkyl glycoside is 2.5.

[0110] The block copolymer is a composition of epoxy block copolymers; the composition of the epoxy block copolymer is BASF L64 (weight average molecular weight 2900Da) and BASF L87 (weight average molecular weight 7800Da), and the mass ratio of the two is 1.8:0.5.

[0111] The filling particles are modified titanium oxide particles; the preparation method of modified titanium oxide particles comprises the following steps, measured in parts by mass: S1: adding 3 parts of titanium oxide and 10 parts of ammonia water into 50 parts of anhydrous ethanol, stirring and mixing evenly; S2: adding an aqueous solution containing 6 parts of ethyl orthosilicate (50 parts in total) dropwise into the mixture obtained in S1, the dropping reaction time is 2 hours, and the dropping reaction temperature is 50°C; S3: after the dropping reaction is completed, centrifuge and wash with anhydrous ethanol and then dry to obtain a solid powder.

[0112] The second aspect of the present comparative example also provides a method for preparing the above-mentioned bio-based gel composition, and the preparation method comprises the following steps: S1: adding the required ingredients to the sol in the gelling tank for mixing, and the mixing temperature is 85°C. After the mixing is completed, adding to the pill dropping machine and adding flavor to prepare wet pills; S2: placing the wet pills in a pill washing barrel for washing, and after the washing is completed, transferring to a ventilated rotating cage for drying at 55°C; S3: after the drying is completed, transferring to a vibrating sieving machine for sieving 10 meshes as required, and after completion, the bio-based gel composition is obtained.

[0113] The flavor is sweet orange flavor; the added amount is 0.5wt% of the total amount of S1 sol.

[0114] Comparative Example 3

[0115] Comparative Example 3 The first aspect provides a bio-based gel composition, in which the raw materials include, by mass: 55 parts of main glue, 25 parts of auxiliary glue, 4 parts of metal compound, 30 parts of auxiliary agent, 10 parts of filling particles, and 1650 parts of deionized water.

[0116] The main gelatin is carrageenan and agar; carrageenan was purchased from the food-grade carrageenan products sold by Hubei Mingtuo Biotechnology Co., Ltd.; agar was purchased from the food-grade agar products sold by Wuhan Juxinlai Biotechnology Co., Ltd.; the mass ratio of carrageenan to agar is 1:1.

[0117] The auxiliary gum is a composition of low acyl gellan gum and high acyl gellan gum; the mass ratio of low acyl gellan gum to high acyl gellan gum is 1:2; low acyl gellan gum and high acyl gellan gum are purchased from food grade low acyl gellan gum and high acyl gellan gum products sold by Guangzhou Huayu Biotechnology Co., Ltd., respectively.

[0118] The metal compounds are potassium chloride and calcium chloride; the mass ratio of potassium chloride to calcium chloride is 3.5:0.5; and the average particle size of potassium chloride and calcium chloride is 0.1 μm.

[0119] The auxiliary agents are water retaining agent and surfactant; the mass ratio of the water retaining agent to the surfactant is 2:1.

[0120] The water retaining agent is sodium alginate, glycerol and sorbitol, and the mass ratio of the three is 2:13:8.

[0121] The surfactants are block copolymers and alkyl glycosides, and the mass ratio of the block copolymers to the alkyl glycosides is 2:5; the alkyl glycoside is purchased from the APG0810 model product sold by Shanghai Hongzhuang Chemical Technology Co., Ltd., and the average degree of polymerization of the alkyl glycoside is 2.5.

[0122] The block copolymer is a composition of epoxy block copolymers; the composition of the epoxy block copolymer is BASF L64 (weight average molecular weight 2900Da) and BASF L87 (weight average molecular weight 7800Da), and the mass ratio of the two is 1.8:0.5.

[0123] The filling particles are modified titanium oxide particles; the preparation method of modified titanium oxide particles comprises the following steps, measured in parts by mass: S1: adding 3 parts of titanium oxide and 10 parts of ammonia water into 50 parts of anhydrous ethanol, stirring and mixing evenly; S2: adding an aqueous solution containing 6 parts of ethyl orthosilicate (50 parts in total) dropwise into the mixture obtained in S1, the dropping reaction time is 2 hours, and the dropping reaction temperature is 50°C; S3: after the dropping reaction is completed, centrifuge and wash with anhydrous ethanol and then dry to obtain a solid powder.

[0124] The second aspect of the present comparative example also provides a method for preparing the above-mentioned bio-based gel composition, and the preparation method comprises the following steps: S1: adding the required ingredients to the sol in the gelling tank for mixing, and the mixing temperature is 85°C. After the mixing is completed, adding to the pill dropping machine and adding flavor to prepare wet pills; S2: placing the wet pills in a pill washing barrel for washing, and after the washing is completed, transferring to a ventilated rotating cage for drying at 55°C; S3: after the drying is completed, transferring to a vibrating sieving machine for sieving 10 meshes as required, and after completion, the bio-based gel composition is obtained.

[0125] The flavor is sweet orange flavor; the added amount is 0.5wt% of the total amount of S1 sol.

[0126] Comparative Example 4

[0127] Comparative Example 4 The first aspect provides a bio-based gel composition, in which the raw materials include, by mass: 55 parts of main glue, 25 parts of auxiliary glue, 4 parts of metal compound, 30 parts of auxiliary agent, 10 parts of filling particles, and 1650 parts of deionized water.

[0128] The main gelatin is carrageenan and agar; carrageenan is purchased from the food-grade carrageenan products sold by Hubei Mingtuo Biotechnology Co., Ltd.; agar is purchased from the food-grade agar products sold by Wuhan Juxinlai Biotechnology Co., Ltd.; the mass ratio of carrageenan to agar is 4:1.5.

[0129] The auxiliary gum is a composition of low acyl gellan gum and high acyl gellan gum; the mass ratio of low acyl gellan gum to high acyl gellan gum is 2.9:0.1; low acyl gellan gum and high acyl gellan gum are purchased from food grade low acyl gellan gum and high acyl gellan gum products sold by Guangzhou Huayu Biotechnology Co., Ltd., respectively.

[0130] The metal compounds are potassium chloride and calcium chloride; the mass ratio of potassium chloride to calcium chloride is 3.5:0.5; and the average particle size of potassium chloride and calcium chloride is 0.1 μm.

[0131] The auxiliary agents are water retaining agent and surfactant; the mass ratio of the water retaining agent to the surfactant is 2:1.

[0132] The water retaining agent is sodium alginate, glycerol and sorbitol, and the mass ratio of the three is 2:13:8.

[0133] The surfactants are block copolymers and alkyl glycosides, and the mass ratio of the block copolymers to the alkyl glycosides is 2:5; the alkyl glycoside is purchased from the APG0810 model product sold by Shanghai Hongzhuang Chemical Technology Co., Ltd., and the average degree of polymerization of the alkyl glycoside is 2.5.

[0134] The block copolymer is an epoxy block copolymer; the composition of the epoxy block copolymer is BASF L64 (weight average molecular weight 2900 Da).

[0135] The filling particles are modified titanium oxide particles; the preparation method of modified titanium oxide particles comprises the following steps, measured in parts by mass: S1: adding 3 parts of titanium oxide and 10 parts of ammonia water into 50 parts of anhydrous ethanol, stirring and mixing evenly; S2: adding an aqueous solution containing 6 parts of ethyl orthosilicate (50 parts in total) dropwise into the mixture obtained in S1, the dropping reaction time is 2 hours, and the dropping reaction temperature is 50°C; S3: after the dropping reaction is completed, centrifuge and wash with anhydrous ethanol and then dry to obtain a solid powder.

[0136] The second aspect of the present comparative example also provides a method for preparing the above-mentioned bio-based gel composition, and the preparation method comprises the following steps: S1: adding the required ingredients to the sol in the gelling tank for mixing, and the mixing temperature is 85°C. After the mixing is completed, adding to the pill dropping machine and adding flavor to prepare wet pills; S2: placing the wet pills in a pill washing barrel for washing, and after the washing is completed, transferring to a ventilated rotating cage for drying at 55°C; S3: after the drying is completed, transferring to a vibrating sieving machine for sieving 10 meshes as required, and after completion, the bio-based gel composition is obtained.

[0137] The flavor is sweet orange flavor; the added amount is 0.5wt% of the total amount of S1 sol.

[0138] Comparative Example 5

[0139] Comparative Example 5 The first aspect provides a bio-based gel composition, in which the raw materials include, by mass: 55 parts of main glue, 25 parts of auxiliary glue, 4 parts of metal compound, 30 parts of auxiliary agent, 10 parts of filling particles, and 1650 parts of deionized water.

[0140] The main gelatin is carrageenan and agar; carrageenan is purchased from the food-grade carrageenan products sold by Hubei Mingtuo Biotechnology Co., Ltd.; agar is purchased from the food-grade agar products sold by Wuhan Juxinlai Biotechnology Co., Ltd.; the mass ratio of carrageenan to agar is 4:1.5.

[0141] The auxiliary gum is a composition of low acyl gellan gum and high acyl gellan gum; the mass ratio of low acyl gellan gum to high acyl gellan gum is 2.9:0.1; low acyl gellan gum and high acyl gellan gum are purchased from food grade low acyl gellan gum and high acyl gellan gum products sold by Guangzhou Huayu Biotechnology Co., Ltd., respectively.

[0142] The metal compounds are potassium chloride and calcium chloride; the mass ratio of potassium chloride to calcium chloride is 3.5:0.5; and the average particle size of potassium chloride and calcium chloride is 0.1 μm.

[0143] The auxiliary agents are water retaining agent and surfactant; the mass ratio of the water retaining agent to the surfactant is 2:1.

[0144] The water retaining agent is sodium alginate, glycerol and sorbitol, and the mass ratio of the three is 2:13:8.

[0145] The surfactants are block copolymers and alkyl glycosides, and the mass ratio of the block copolymers to the alkyl glycosides is 2:5; the alkyl glycoside is purchased from the APG0810 model product sold by Shanghai Hongzhuang Chemical Technology Co., Ltd., and the average degree of polymerization of the alkyl glycoside is 2.5.

[0146] The block copolymer is a composition of epoxy block copolymers; the composition of the epoxy block copolymer is BASF L64 (weight average molecular weight 2900Da) and BASF L87 (weight average molecular weight 7800Da), and the mass ratio of the two is 0.5:1.

[0147] The filling particles are modified titanium oxide particles; the preparation method of modified titanium oxide particles comprises the following steps, measured in parts by mass: S1: adding 3 parts of titanium oxide and 10 parts of ammonia water into 50 parts of anhydrous ethanol, stirring and mixing evenly; S2: adding an aqueous solution containing 6 parts of ethyl orthosilicate (50 parts in total) dropwise into the mixture obtained in S1, the dropping reaction time is 2 hours, and the dropping reaction temperature is 50°C; S3: after the dropping reaction is completed, centrifuge and wash with anhydrous ethanol and then dry to obtain a solid powder.

[0148] The second aspect of the present comparative example also provides a method for preparing the above-mentioned bio-based gel composition, and the preparation method comprises the following steps: S1: adding the required ingredients to the sol in the gelling tank for mixing, and the mixing temperature is 85°C. After the mixing is completed, adding to the pill dropping machine and adding flavor to prepare wet pills; S2: placing the wet pills in a pill washing barrel for washing, and after the washing is completed, transferring to a ventilated rotating cage for drying at 55°C; S3: after the drying is completed, transferring to a vibrating sieving machine for sieving 10 meshes as required, and after completion, the bio-based gel composition is obtained.

[0149] The flavor is sweet orange flavor; the added amount is 0.5wt% of the total amount of S1 sol.

[0150] Characterization Tests:

[0151] The FT-IR spectral analysis of carrageenan and agar used in the embodiment can be performed by the following test method. First, carrageenan and agar samples are prepared into uniform flakes or powders and placed in the sample chamber of the FT-IR instrument to ensure good contact between the sample and the instrument. Then, according to the guidance of the instrument manual, the instrument parameters are set, including selecting a suitable light source and detector, setting the scanning range and resolution, etc. Next, the scanning process is started, and the instrument emits infrared radiation to interact with the sample, and detects and records the absorption spectrum. The generated spectrum is analyzed by observing and interpreting the absorption peaks and troughs, with particular attention to the characteristic peaks related to the molecular structure of carrageenan and agar.

[0152] The X-ray diffraction (XRD) technique can be used to characterize the physical phases of potassium chloride and calcium chloride. First, prepare the metal chloride sample and prepare it into an appropriate form, such as flakes or powder. Place the sample in the XRD instrument and ensure good contact between the sample and the instrument. Then, select the appropriate X-ray wavelength as needed and set the instrument parameters, such as scanning range, scanning speed, and angular resolution. Start the scanning process, the instrument will emit an X-ray beam to irradiate the sample and record the scattered X-ray signal. By analyzing the scattered X-ray signal, the diffraction pattern of the sample can be obtained. Based on the position, intensity, and shape of the diffraction peaks in the diffraction pattern, the crystal structure and phase information of the metal chloride can be determined. The physical phases of potassium chloride and calcium chloride can be further confirmed by comparing with a known standard phase database.

[0153] like Figure 1 The FT-IR spectra of carrageenan and agar are shown. The FT-IR spectra of agar and carrageenan are almost the same, which is due to their similar molecular chain structures. The main peak is located at 2923cm -1 , caused by the stretching of the C-H bond, while 1075cm -1 and 930cm -1 The peak position of carrageenan is related to the 3,6-anhydrogalactose bridge. Compared with agar, the spectrum of carrageenan is at 1255 cm -1 A larger absorption band is shown around 3400 cm, corresponding to the stretching of O=S=O. -1 The peak position is attributed to the stretching of the OH bond. It can be clearly seen that the addition of carrageenan to agar causes the OH bond band to shift from the higher frequency 3432 cm -1 Towards the lower frequency 3406cm -1 Move. Figure 2 Shown is the XRD phase analysis of metal chlorides. It can be seen that only potassium chloride and potassium chloride exist, proving the validity of the phase.

[0154] Performance Test:

[0155] 1. Stability test: The gel composition bursting beads prepared in the embodiment and the comparative example were subjected to stability test. 50 gel bursting beads were taken, and the average mass of the gel bursting beads was tested and recorded. The beads were stored in a constant temperature and humidity chamber at 60°C and 75% humidity for 10 days. After 10 days, the beads were taken out and observed for obvious mold, bacterial growth, and gel melting and sticking. If any, they were recorded as unqualified, otherwise, they were qualified, and the pass rate of the overall test was recorded. On the other hand, the above-mentioned qualified gel bursting beads were selected for testing, and the percentage difference between the average mass of the gel bursting beads and the average mass of the gel bursting beads before the test was calculated. The test results were recorded in Table 1.

[0156] 2. Antibacterial property: Test the bacterial concentration of the gel composition bursting beads prepared in the examples and comparative examples and record it. Select additional samples of the same batch of examples and comparative examples, store them in a constant temperature and humidity chamber at 45°C and 75% humidity for 3 days, then take them out and test the bacterial concentration of the gel bursting beads again. Calculate the incremental percentage of the bacterial concentration before and after the test. The incremental percentage of the bacterial concentration (%) = (bacterial concentration after the test - bacterial concentration before the test) / bacterial concentration before the test × 100%. The average value of the 5 tests is recorded in Table 1.

[0157] Table 1

[0158]

[0159] From the examples and comparative examples of the present application and the data results in Table 1, it can be known that the examples 1 to 3 of the necessary technical solutions given in the present application have achieved excellent results in the stability test and antibacterial test of the bio-based gel composition, which enables it to effectively replace the existing popping bead products in the popping bead, and play an excellent antibacterial and stability function, and is conducive to the improvement of the production efficiency of the popping bead; in comparative examples 1 to 3, due to the change in the mass ratio of low acyl gellan gum and high acyl gellan gum or the addition of low acyl gellan gum alone, the internal cohesion of the gel composition system cannot be effectively enhanced, and a good entangled molecular chain network cannot be formed, which leads to a decrease in gel efficiency and internal tightness, greatly reducing the barrier efficiency of the gel composition for external substances, and then significantly reducing various performance aspects. In comparative examples 4 to 5, because a specific ratio of epoxy block copolymers is not used, a good multi-layer protection structure cannot be described in the gel system, and the interface resistance is significantly reduced compared with the examples, so that a good barrier effect on active molecules cannot be achieved, so the stability is significantly reduced.

Claims

1. A bio-based gel composition, characterized in that: In parts by mass, the raw materials include: 50-70 parts of main glue, 25-35 parts of auxiliary glue, 2-10 parts of metal compound, 10-50 parts of auxiliary agent, 10-20 parts of filling particles, and 1600-1800 parts of deionized water; The mass ratio of the main glue to the auxiliary glue is (5-6): (2.5-3); The main gelatin is carrageenan and agar; the mass ratio of carrageenan to agar is (3-6): (1-4); The auxiliary gum is a combination of low acyl gellan gum and high acyl gellan gum; The mass ratio of the low acyl gellan gum to the high acyl gellan gum is (2-4): (0.05-0.5); The metal compound is at least one of sodium chloride, potassium chloride, calcium chloride, sodium carbonate, sodium bicarbonate, and magnesium chloride; The average particle size of the metal compound is 0.05-0.3 μm; The auxiliary agent is a water retaining agent and a surfactant; the mass ratio of the water retaining agent to the surfactant is (1.5-3):1; The water retaining agent is sodium alginate, glycerol and sorbitol; the mass ratio of sodium alginate, glycerol and sorbitol is (0.3-7): (6-30): (3-20); The surfactant is a block copolymer and an alkyl polyglycoside; The mass ratio of the block copolymer to the alkyl glycoside is (1-3): (3-8); The block copolymer is a composition of epoxy block copolymers, and the composition of epoxy block copolymers is a combination of BASF L64 and BASF L87, and the mass ratio of the two is (1-2.5): (0.1-1); The polymerization degree of the alkyl glycoside is 2 to 3.

5.

2. The bio-based gel composition according to claim 1, characterized in that: The metal compounds are potassium chloride and calcium chloride; the mass ratio of potassium chloride to calcium chloride is (2-5): (0.1-1).

3. A method for preparing the bio-based gel composition according to claim 1, characterized in that: Preparation method The following steps are involved: S1: Add the required ingredients into the sol in the gelling tank and mix them at a mixing temperature of 80-90°C. After mixing, add them into a pill-dropping machine and add flavors to prepare wet pills; S2: Place the wet pills into a pill-washing barrel for washing. After washing, transfer them into a ventilated cage for drying at 50-60°C; S3: After drying, transfer them into a vibrating sieving machine for sieving 1-50 mesh as required. After completion, a bio-based gel composition is obtained.

4. An application of the bio-based gel composition according to claim 1, characterized in that: The invention comprises application of the bio-based gel composition in preparation of explosive beads.

Citation Information

Patent Citations

  • Botanical hollow capsule, and preparation technology and preparation system thereof

    CN102816347A

  • Brittle wall material of cigarette blasting bead

    CN112574475A